2019
DOI: 10.1186/s12955-019-1226-6
|View full text |Cite
|
Sign up to set email alerts
|

Do modern family planning methods impact women’s quality of life? Jordanian women’s perspective

Abstract: Background Although Jordan has made progress in meeting Family Planning (FP) needs in last decades, recently the use of FP methods has declined significantly. Women’s personal experiences, knowledge, and perceptions of how a FP method might impact their quality of life (QoL) can influence FP decisions. However, a lack of comprehensive understanding of the impact of modern FP methods on women’s QoL continues to exist among Jordanian couples. Therefore, this study aimed to investigate the relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 64 publications
5
17
1
Order By: Relevance
“…Alyahya et al study revealed that women who had undergone permanent sterilization had lower QOL scores in all of the four domains. Also, experience side effects and vaginal bleeding in these women are related to QOL impairment [ 18 ]. In contrast, the results of Li et al [ 16 ] study showed that female sterilization have a positive impact on women’s QOL.…”
Section: Discussionmentioning
confidence: 99%
“…Alyahya et al study revealed that women who had undergone permanent sterilization had lower QOL scores in all of the four domains. Also, experience side effects and vaginal bleeding in these women are related to QOL impairment [ 18 ]. In contrast, the results of Li et al [ 16 ] study showed that female sterilization have a positive impact on women’s QOL.…”
Section: Discussionmentioning
confidence: 99%
“…Alyahya et al study revealed that women who had undergone permanent sterilization had lower QOL scores in all of the four domains. Also, experience side effects and vaginal bleeding in these women are related to QOL impairment (18). In contrast, the results of Li et al study showed that female sterilization have a positive impact on women's QOL (16).…”
Section: Discussionmentioning
confidence: 92%
“…Alyahya et al study revealed that women who had undergone permanent sterilization had lower QOL scores in all of the four domains. Also, experience side effects and vaginal bleeding in these women are related to QOL impairment (8). In contrast, the results of Pauls et al study showed that surgical interventions such as TL have a positive impact on women's QOL (15).…”
Section: Discussionmentioning
confidence: 94%
“…There are conflicting results on the influence of TL on quality of life (QOL) (8,6). Some studies in developing countries with high maternal mortality rates have reported the positive impact of TL on the women's QOL (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation